2017
DOI: 10.1038/s41598-017-00321-6
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of Echinacea chloroplast genomes: Implications for future botanical identification

Abstract: Echinacea is a common botanical used in dietary supplements, primarily to treat upper respiratory tract infections and to support immune function. There are currently thought to be nine species in the genus Echinacea. Due to very low molecular divergence among sister species, traditional DNA barcoding has not been successful for differentiation of Echinacea species. Here, we present the use of full chloroplast genomes to distinguish between all 9 reported species. Total DNA was extracted from specimens stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 51 publications
4
45
1
2
Order By: Relevance
“…Chen et al [14] reported that there were no barcode gaps for Curcuma L. Zingiberaceae species with four chloroplast barcoding regions (matK, rbcL, trnH-psbA, and trnL-F). Recently this issue was also encountered with closely related Echinacea species in our own study [15].…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Chen et al [14] reported that there were no barcode gaps for Curcuma L. Zingiberaceae species with four chloroplast barcoding regions (matK, rbcL, trnH-psbA, and trnL-F). Recently this issue was also encountered with closely related Echinacea species in our own study [15].…”
mentioning
confidence: 66%
“…Both the consensus sequence from the reference-guided assembly and the contigs from the de novo assembly were imported into Geneious Pro 9.1.4 [25], and then those contigs were mapped onto the consensus sequence. The mapped contigs were manually checked to align them with the consensus sequence obtained using referenced-guided assembly [15,26]. The final sequence of the chloroplast genome of each species is the ordered sequence of those mapped contigs.…”
Section: Genome Assembly and Annotationmentioning
confidence: 99%
“…The most variable noncoding regions included trnH-GUG-psbA, trnR-UCU-atpA, trnC-GCA-petN, ycf3-trnS-GGA, and trnL-UAA-trnF-GAA in six Adoxaceae chloroplast genomes 32 ; and TrnN-GUU-ndhF is the hotspot region in Capsicum 36 . The regions with the highest percentage of sequence variation were ccs-trnL-UAG, psbI-trnS-GCU, rpl32-ndhF, trnT-UGU-TrnL-UAA and petN-psbM in Echinacea 19 . In three closely related East Asian wild roses, matK-trnK, psbI-trnS-trnG, rps16-trnG, rpoB-trnC and rps4-trnT were the most divergent intergenic regions, with Pi values exceeding 0.006 28 .…”
Section: Genetic Diversity In Different Chloroplast Regions the Genementioning
confidence: 99%
“…The evolution rate or genetic diversity of different regions of the chloroplast genome varies greatly, and the successful development of common primers in those high-variability regions make these loci widely used in the study of phylogenetic relationships among species; among these loci, matK and rbcL are most commonly used 16,17 . With the application of high-throughput sequencing technology, the cost of sequencing has been greatly reduced, which makes it possible to reveal the phylogenetic relationships among species by using the genetic information of the whole chloroplast genome in many plant groups 15,[18][19][20] . The abundant genetic variation information and maternal genetic characteristics of the chloroplast genome are particularly suitable for reconstructing the phylogeny of low-level taxonomic hierarchies with complex relationships.…”
mentioning
confidence: 99%
“…Effective means of identifying Bixa for authentication purposes in food and other commercial products is important. Recently, use of whole genomes as references (as opposed to DNA barcodes [12][13][14][15][16] for species identification programs has provided important reference databases and a greater variety of genetic markers that can be applied to identification/authentication protocols [17,18]. Development of species specific markers that confirm the identify of natural products, relies on well curated databases of multiple high quality accessions [16].…”
Section: Introductionmentioning
confidence: 99%